The asset market view on flexible exchange rates: A critical comment - Thusnelda Tivig (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1987)
The more recent asset market literature on flexible exchange rates seems to share the opinion that it is not possible to treat the stock-flow interaction on the adjustment path to a new long-run equilibrium adequately in continuous time. The present paper discloses some severe inconsistencies between the verbal and formal formulation of the asset market ap-proach (AMA) that are linked to this proposition and argues that the AMA has not reached its target yet. A possible Solution is outlined.
Keywords: 330; Monetäre Wechselkurstheorie; Internationaler Finanzmarkt; Theorie